Comunidades cristãs: eco da voz de Jesus - o desafio da inclusão homossexual e transexual à luz do chamado de Paulo o Apóstolo - Ferreira, Edi Gomes (2019)
This research is an exercise in reflection in Practical Theology, based on reports collected from people in the homo and transsexual condition, to understand the ecclesiastical challenge of inclusion and acceptance in the churches. For this, this research will promote a look at the call to holiness in Saul, on his way to Damascus, and his experience with the first Christian communities. This research establishes a relationship with current accounts of homosexuals or transsexuals who desire and believe that they can live the gospel values but who feel excluded and/or persecuted in their condition. The primary objective is to stimulate a reflection on the Pauline experience which, in pursuing the Christian communities in the name of an ideal of religious life, hears the voice of Jesus who says: "Saul, Saul why do you persecute me?" (Acts 9: 4). This research applies “epoché”, proper to the phenomenological method, to let come to the light and reach to our ears the cry, often muffled, of people who seek to live the Christian values and a way of sanctity without denying their own condition. It is intended to know if they use, reverberate the voice of Jesus and cry, "why persecute us?". Strategically suspending the tables of preestablished values, this research wants to show the theological-pastoral reasons that presuppose, in the application of the "mercy principle "(Cf. GE, 46), listening to these voices